2011
DOI: 10.5761/atcs.cr.10.01540
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Replacement and Graft Replacement of the Ascending Aorta Using Deep Hypothermic Circulatory Arrest in a Patient with Myelodysplastic Syndrome

Abstract: A 73-year-old woman with a 10-year history of myelodysplastic syndrome (MDS) had severe aortic regurgitation (AR) and an ascending thoracic aortic aneurysm (TAA) with a maximum diameter of 55 mm. By retrograde cerebral perfusion (RCP) in the patient under deep hypothermic circulatory arrest (DHCA), we replaced the ascending aorta graft and aortic valve. After surgery, we periodically administered granulocyte colony-stimulating factor (GCSF) with platelet aggregation. On postoperative day 20, the patient had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…5,7 The literature contains very few case presentations on the performance of aortic valve surgery on patients with myelodysplastic syndrome while there are no publications on the use of the TAVI method on these cases. 5…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,7 The literature contains very few case presentations on the performance of aortic valve surgery on patients with myelodysplastic syndrome while there are no publications on the use of the TAVI method on these cases. 5…”
Section: Discussionmentioning
confidence: 99%
“…4 Based on a comprehensive investigation of the literature, we found that only about 10 cases of heart surgery in patients with MDS have been reported previously and most of them were operated on due to an isolated CABG or a single valve replacement. 5,7 The literature contains very few case presentations on the performance of aortic valve surgery on patients with myelodysplastic syndrome while there are no publications on the use of the TAVI method on these cases. 5 As a treatment method that gives hope to patients with severe aortic stenosis who are under high surgical risk, transcatheter aortic valve implantation has been increasingly used, with an extending range of indications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations